Altered left atrial appendage function associated with cardioembolic stroke in patients with rheumatic heart disease - Mansuri, Zeeshan H.; Brahmbhatt, Jit H.; Singhal, Roopesh R.; Natarajan, Karthik (International Journal of Advances in Medicine, 2021)
Background: Left atrial appendage (LAA) is usually the first site for thrombus formation in rheumatic heart disease (RHD). LAA function is altered in RHD which may predispose it to thrombus formation. The aim of this study was to determine an association between function of LAA and cardioembolic stroke. Methods:Total 132 patients with RHD were studied by means of transthoracic echocardiography and/or transesophageal echocardiography and left atrial (LA) size, LAA ejection fraction (EF) and peak flow velocities were measured. These patients were followed up for 18 months with reference to development of cardioembolic stroke. Results: Seventy nine patients had atrial fibrillation (AF), of which 34 had thrombus in LAA. Out of 53 patients with sinus rhythm, 5 had LAA thrombus. Mean LAA EF was significantly lower in patients with thrombus in LAA, so was the peak flow velocity (both variables p<0.0001). Saw tooth LAA outflow velocity pattern was visible in 30 (80%) patients with LAA thrombus versus 20 (28%) patients without LAA thrombus. Total 14 patients experienced cardioembolic stroke. Patients with cardioembolic stroke had lower mean LAA EF and peak flow velocity as compared to patients without cardioembolic stroke. Conclusions:Increased LAA size, reduced LAA EF and reduced peak flow velocity are associated with increased risk of cardioembolic stroke. LAA evaluation should be mandatory in deciding treatment strategies in patients with RHD and AF.